PENGARUH PROFESIONALISME BIROKRASI DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA BIRO PELAYANAN SOSIAL DASAR SETDA JABAR - Bhagya, Tombak Gapura (Prodi Administrasi Publik FISIP UNPAS, 2020)
This research is based on the main problem, namely low employee performance. This is allegedly due to the incomplete professionalism of the Bureaucracy and the Development of Human Resources at the West Java Regional Secretariat for Basic Social Services. Lack of Employee Performance can be seen from several indicators, namely: the accuracy of low quality work, low work cooperation and low employee work attitudes. Based on these facts, the allegations arise because of bureaucratic professionalism and optimal human resource development. The research method used was an explanatory survey, using a quantitative approach through Path Analysis. The results showed that the professionalism of the bureaucracy and the development of natural resources had a significant influence on the performance of employees at the West Java Regional Secretariat of Social Services. Keywords: Profesionalism, Development, performance